Necessary and sufficient conditions on the Schur convexity of a bivariate mean - Yin, Hong-Ping; Liu, Xi-Min; Wang, Jing-Yu; Guo, Bai-Ni (AIMS mathematics, 2021)
In the paper, the authors find and apply necessary and sufficient conditions for a bivariate mean of two positive numbers with three parameters to be Schur convex or Schur harmonically convex respectively.